INHIBITION OF HEART VENTRICULAR FUNCTION OF RAT BY BISPHENOL A THROUGH OXIDATIVE STRESS INDUCED INJURY OF VENTRICULAR TISSUE. - PANCHALI TARAFDER; KAUSHIK SARKAR; PARTHA P. NATH; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2013)
The toxic effect of Bisphenol A (BPA) on heart ventricular function has not been reported till date. So the present study was undertaken to examine the effect of BPA on ventricular function in rat models. BPA (50mg/kgBW/day) was administered for 20 and 30 days by oral-gavage. The rats were sacrificed by cervical dislocation on 24th hour after last treatment. Paraffin embedded ventricular tissue sections were stained with hematoxylin-eosin. Significant degenerative changes were observed in hematoxylin-eosin stained ventricular tissue sections of test rats. The activities of antioxidant enzymes like- superoxide dismutase, catalase, glutathione reductase and glutathione peroxidase were seen to be decreased significantly in both durations; while, the level of malondialdehyde, a biomarker of lipid peroxidation, was increased than dimethyl sulfoxide (DMSO, vehicle of BPA) treated rats. In conclusion, BPA inhibits ventricular function in rat presumably by producing oxidative stress induced injury of ventricular tissue.